The Human Factors YY1 and LSF Repress the Human Immunodeficiency Virus Type 1 Long Terminal Repeat via Recruitment of Histone Deacetylase 1 - Coull, Jason J. (American Society for Microbiology, 2000)
Enigmatic mechanisms restore the resting state in activated lymphocytes following human immunodeficiency virus type 1 (HIV-1) infection, rarely allowing persistent nonproductive infection. We detail a mechanism whereby cellular factors could establish virological latency. The transcription factors YY1 and LSF cooperate in repression of transcription from the HIV-1 long terminal repeat (LTR). LSF recruits YY1 to the LTR via the zinc fingers of YY1. The first two zinc fingers were observed to be sufficient for this interaction in vitro. A mutant of LSF incapable of binding DNA blocked repression. Like other transcriptional repressors, YY1 can function via recruitment of histone deacetylase (HDAC). We find that HDAC1 copurifies with the LTR-binding YY1-LSF repressor complex, the domain of YY1 that interacts with HDAC1 is required to repress the HIV-1 promoter, expression of HDAC1 augments repression of the LTR by YY1, and the deacetylase inhibitor trichostatin A blocks repression mediated by YY1. This novel link between HDAC recruitment and inhibition of HIV-1 expression by YY1 and LSF, in the natural context of a viral promoter integrated into chromosomal DNA, is the first demonstration of a molecular mechanism of repression of HIV-1. YY1 and LSF may establish transcriptional and virological latency of HIV, a state that has recently been recognized in vivo and has significant implications for the long-term treatment of AIDS.